1977
DOI: 10.1029/js082i028p04625
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and mineralogical interpretation of the Viking inorganic chemical results

Abstract: The elemental analyses whose basis is described in the preceding two papers represent the composition of samples of Martian fines; the only undetermined major constituents thought to be present are H2O, CO2, Na2O, and possibly NOx. The samples are principally silicate particles, with some admixture of oxide and probably carbonate minerals; the fines appear to have been indurated to a variable degree by a sulfate‐rich intergranular cement. The overall elemental composition is dissimilar to any single known mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
144
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(153 citation statements)
references
References 45 publications
6
144
0
Order By: Relevance
“…For these reasons, calibration targets were created with (1) a clay mineral component that has been processed in a manner (heating to 1000°C) that prevents hydration/dehydration cycling yet preserves the anhydrous chemical composition and (2) a relatively stable sulfate component. Past missions have shown that sediments on Mars incorporate a significant amount of basaltic detritus (e.g., Toulmin et al 1977;); therefore we have included a basaltic component in these targets. The clay samples chosen were Fe-rich smectite (nontronite) and an aluminous clay mineral (kaolinite).…”
Section: Preparation Methods and Selection Of Target Compositionsmentioning
confidence: 99%
“…For these reasons, calibration targets were created with (1) a clay mineral component that has been processed in a manner (heating to 1000°C) that prevents hydration/dehydration cycling yet preserves the anhydrous chemical composition and (2) a relatively stable sulfate component. Past missions have shown that sediments on Mars incorporate a significant amount of basaltic detritus (e.g., Toulmin et al 1977;); therefore we have included a basaltic component in these targets. The clay samples chosen were Fe-rich smectite (nontronite) and an aluminous clay mineral (kaolinite).…”
Section: Preparation Methods and Selection Of Target Compositionsmentioning
confidence: 99%
“…The surface chemistry experiments of the Viking landers detected sulfates in the soil with abundances of 5 to 10 wt% (Toulmin et al 1977). More recently, the Spirit and Opportunity rover experiments reported the detection of sulfates (in particular ferric sulfates and magnesium sulfates) at the Gusev and Meridiani sites (Squyres et al 2004;Rieder et al 2004;Johnson et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…The palagonitization of basaltic glass is considered to be a viable process on Mars (Toulmin et al, 1977;Allen et al, 1981;Gooding, 1992). Allen et al (1981) specifically suggested that hydrothermal palagonitization could take place down to depths of about 150 m, and that after the initial quenching of magma with ground ice, further low-temperature alteration could continue for some time afterward through the interaction of subsurface waters with cooling volcanic material.…”
mentioning
confidence: 99%